Copper-containing spherical mesoporous silicates prepared by template-ion exchange: A multitechnique characterization and oxidation properties - Chanquia, Corina Mercedes (2012)
M41S type mesoporous silicate particles with spherical morphology containing copper nano-species were successfully synthesized by the template-ion exchange (TIE) method and compared with those synthesized by the direct hydrothermal (DHT) method. Various techniques including XRD, AAS, adsorption/ desorption of N2, SEM, TEM, TGA, UV–Vis-DRS, TPR, XPS and FT-IR-Py, were employed for the nanocatalysts characterization. A narrow distribution of silicate particle size between 2 and 3 lm, and a primary mesoporosity were evidenced by electronic microscopy, even for loadings of copper of about 7 wt.%. All the materials exhibited a good structural regularity, besides of high surface areas (>1000 m2/g) and pore volumes ( 1 cm3/g). A secondary mesoporosity, likely caused by the hydrothermal treatment during the TIE process, was also detected. This new synthesis method showed the advantage of promoting the introduction of copper nano-species to the mesostructure (isolated Cud+ species and [Cud+. . .Od . . .Cud+]n clusters), minimizing the bulk CuO formation. The coexistence of both oxidation states 1+ and 2+ (d+) in the major copper species present in these catalysts could be inferred. In addition, all of the samples only showed Lewis acid sites. The cyclohexene oxidation with H2O2 has been studied as a catalytic test: the highly dispersed Cud+ species on the mesopore walls, obtained by TIE method, have been suggested as the main active sites for the oxidation. The allylic oxidation has mainly taken place, with the formation of 2-cyclohexen-1-one and 2-cyclohexen-1-ol as major products.